Application of theory of planned behavior in measuring the behavior to reduce plastic consumption among students at Universiti Putra Malaysia, Malaysia - Syed Hasan, Sharifah Nur Munirah; Harun, Rosta; Lim, Kuang Hock (Elsevier, 2015)
This study was conducted to identify the relationship between variables that affect behavioral intention among UPM students in reducing plastic consumption. A survey was done using validated questionnaire and distributed among 393 respondents of UPM students. The study revealed that perceived behavioral control (PCB) shows the highest relationship with behavior compared to other variables. There was statistically significant of behavior difference between genders. However, there was no statistically significant difference of behavior between level of education and stream of study (science and social science).